Enhancing tourism competitiveness of Hong Kong via tourism planning: A comparative case study between Hong Kong and Singapore - Kaewta Muangasame (2018)
This article aims to recommend tourism planning in Hong Kong (HK). A comparison case study of tourism planning between Singapore and Hong Kong is discussed. Secondary data from web sites, observations and in-depth interviews of ten residents and ten tourists was conducted to investigate tourism planning in the two countries. The study discloses that the HK government should consider adopting a long term oriented plan and implement an integrated approach with their tourism planning. Sustainability issues, land management and carrying capacity should be addressed by HK tourism planners. Lastly, re-structuring of the Tourism board should be considered to improve the efficacy of tourism planning of HK.